Aids to the diagnosis of meningitis in a population with a high prevalence of tuberculosis - Donald, P. R.(Peter Roderick) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.D.) -- University of Stellenbosch, 1985.